A Study on the Values, Interests, Skills, and Career Indecision among Student at the College of Business, Universiti Utara Malaysia - Teo, Aik Chuan (2009)
The purpose of this study was to determine the relationships between values,interests, skills, and career indecision among final year students at the College of Business (COB), Universiti Utara Malaysia. The data for the study was collected from 318 students and analyzed by using the Pearson Correlations analyses. The results of the study indicate negative relationships between values, interests, skills, and career indecision.